Theory and Praxis, Theory and Practice, Practical Theory - Corentin Debailleul; Shimshon Bichler; Jonathan Nitzan (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2016)
This working paper contains an intervention by Corentin Debailleul and an extended reply by Shimshon Bichler and Jonathan Nitzan. The exchange was first posted on the Capital as Power Forum in January 2016. Debailleul's original questions are articulated at greater length here, while Bichler and Nitzan's reply is reproduced as is.
Keywords: 330; capital as power; capitalist mode of power; Marxism